In search of the specific parameter of life - general methodological comments - Szkutnik, Dariusz A. (Biocosmological Association, 2016)
Even in Ancient Times, Aristotle, basing the empirical facts, sought the basis to find the explanation for phenomena and regulatory processes ocurring in living organisms. The key concept in explaining in biophilospohy of Stagirite was the concept of the soul (ψυχή), which was to integrate the developmental processes and explain the specific dynamics of the various living beings. The original ideas and timeless questions of Aristotle became the groundwork on the basis of which the contemporary researchers developed their theories in the overall development of living organisms. German embryologist and philosopher Hans Driesch (1867-1941) took scientific attempt to consolidate and explain a factor responsible for development that is described by me as the parameter of nature. That specific parameter was responsible for entirety of regulating processes in live forms, especially for the totiopotential processes during embryogenesis and regeneration. Despite an attempt of consolidating the mentioned parameter had failed, nevertheless Driesch formed relevant question relating to a way of eventual explanation of specific relationships and mutual interactions of particular structures and integral parts of process in progress of the entire development. Driesch’s method of scientific research brought him eventually to areas of metaphysical explanations which in consequences are not situated in frameworks of strictly scientific explanations, whereby his category of entelecheia remains just as an empty verbal expression requiring new content and fresh methodological solutions. Methodological way of research in range of complementary of scientific explanations related to development of organism should lead to final resolution of the overall course of organic processes by analyzing different research methods. Pyotr Kuzmich Anokhin (1898-1974) was extraordinarily thinking researcher who presented certain scientific alternative in the range of explaining complex regulating processes based on functional systems and their mutual dynamic relationships to reach overall organismal results. Not only his specific statement can be the way of translating morphological regeneration but also it can be scientific method in translation of different complex regulatory processes across each live structure. Perspective of Anokhin proves that methodology of scientific researches may be led on field of pure science without digressions in range of metaphysics often referring to pluralistic method in assigning specific value explaining outer factors to perform a function of being the initiator and regulator in live forms. Author considers a relevance of mentioned problem hence, this short summary is just indication of research scope that requires further solutions and scientific amendments as well as profound philosophical generalization.
The article examines the problem of identifying a specific “parameter of life” capable of accounting for the developmental, regenerative, and organisational processes occurring in living organisms, drawing on the ideas of Aristotle and the research of Hans Driesch. It discusses Driesch’s attempt to formulate such a parameter through the concept of entelechy, highlighting both its methodological significance and its limitations resulting from the transition from scientific inquiry to metaphysical speculation. As a more scientifically grounded alternative, the author presents Pyotr Anokhin’s theory of functional systems, along with contemporary approaches that emphasise the fundamental role of information in the regulation of biological processes.
Keywords: parameter of life; Aristotle; Hans Driesch; entelechy; vitalism; morphogenesis; embryogenesis; regeneration; harmonic-equipotential systems; organic development; biological regulation; theory of functional systems; Pyotr Anokhin